The art of cars 2 - Queen, Ben; Lassester, John.; Paik, Karen; Pixar (Firm) (San Francisco : Chronicle Books, 2011)
Presents storyboards, digital and pencil sketches, and character studies from the animated film'Cars 2.'
Introduction -- The Pacific Ocean -- World grand prix -- Tokyo -- Spycraft -- Paris -- Porto Corsa -- Roads not taken -- London -- Radiator Springs -- Epilogue.
At head of title: Disney-Pixar.
Keywords: Pixar (Firm); Cars 2 (Motion picture) -- Illustrations; Animated films -- United States